Cephalic duodenopancreatectomy: Technical considerations regarding 18 operated cases - Praderi, Raul; Ormaechea, Carlos; Delgado, Bolivar (Cirugía del Uruguay, 1971)
The paper gives an account of the experience based on 18 cephalic duodenopancreatectomies performed in 15 cases of cancer and 3 cases of chronic pancreatitis. There are anatomic considerations on the importance of Henle's venous trunk, the disection of the venae porta, the need to have an exact knowledge of regional arteries and their variants and for complete excission of all nodes. Reconstruction after Child is employed and the authors advise resection of the common bile duct and gall bladder and first jejunal loop. The jejunal loop should not pass behind the mesentery and anastomosis with pancreas should be termino terminal.